DDX58 deficiency leads to triple negative breast cancer chemotherapy resistance by inhibiting Type I IFN-mediated signalling apoptosis - Cao, Shiyu; Long, Xinyi; Xiao, Lin; Zhang, Peichuan; Shen, Mengjia; Chen, Fei; Bao, Chunjuan; Zhong, Xiaorong; Luo, Ting; Ye, Feng (Frontiers in Oncology, 2024)
Introduction Triple-negative breast cancer (TNBC) is characterized by its aggressive nature and absence of specific therapeutic targets, necessitating the reliance on chemotherapy as the primary treatment modality. However, the drug resistance poses a significant challenge in the management of TNBC. In this study, we investigated the role of DDX58 (DExD/H-box helicase 58), also known as RIG-I, in TNBC chemoresistance. Methods The relationship between DDX58 expression and breast cancer prognosis was investigated by online clinical databases and confirmed by immunohistochemistry analysis. DDX58 was knockout by CRISPR-Cas9 system (DDX58-KO), knockdown by DDX58-siRNA (DDX58-KD), and stably over expressed (DDX58-OE) by lentivirus. Western blotting, immunofluorescence and qPCR were used for related molecules detection. Apoptosis was analyzed through flow cytometry (Annexin V/7AAD apoptosis assay) and Caspase 3/7 activity assay. Results Patients with lower expression of DDX58 led to lower rate of pathological complete response (pCR) and worse prognosis by online databases and hospital clinical data. DDX58-KD cells showed multiple chemo-drugs resistance (paclitaxel, doxorubicin, 5-fluorouracil) in TNBC cell lines. Similarly, DDX58-KO cells also showed multiple chemo-drugs resistance in a dosage-dependent manner. In the CDX model, tumours in the DDX58-KO group had a 25% reduction in the tumour growth inhibition rate (IR) compared to wild-type (WT) group after doxorubicin (Dox) treatment. The depletion of DDX58 inhibited proliferation and promoted the migration and invasion in MDA-MB-231 cells. The findings of our research indicated that DDX58-KO cells exhibit a reduction in Dox-induced apoptosis both in vivo and in vitro. Mechanistically, Dox treatment leads to a significant increase in the expression of double-stranded RNAs (dsRNAs) and activates the DDX58-Type I interferon (IFN) signaling pathway, ultimately promoting apoptosis in TNBC cells. Discussion In the process of TNBC chemotherapy, the deficiency of DDX58 can inhibit Dox-induced apoptosis, revealing a new pathway of chemotherapy resistance, and providing a possibility for developing personalized treatment strategies based on DDX58 expression levels.